Μ-distortion around stupendously large primordial black holes. Issue 11 (29th November 2021) - Deng, Heling
Abstract: In a variety of mechanisms generating primordial black holes, each black hole is expected to form along with a surrounding underdense region that roughly compensates the black hole mass. This region will propagate outwards and expand as a shell at the speed of sound in the homogeneous background. Dissipation of the shell due to Silk damping could lead to detectable μ-distortion in the CMB spectrum: if black holes are rare on the last scattering surface, the signal(s) would be pointlike; whereas if there are a sufficient number of them, we could have a uniform distortion in the CMB sky. While the current bound on the average μ-distortion is |μ̅| ≲ 10 -4, the standard ΛCDM model predicts |μ̅| ∼ 10 -8, which could possibly be detected in future missions. It is shown in this work that the non-observation of μ̅ beyond ΛCDM can place a new upper bound on the density of supermassive primordial black holes within the mass range 10 6 M ☉ ≲  M  ≲ 10 15 M ☉ . Furthermore, black holes with initial mass M  ≳ 10 12 M ☉ could leave a pointlike distortion with μ ≳10 -8 at an angular scale ∼ 1° in CMB, and its non-observation would impose an even more stringent bound on the population of these stupendously large primordial black holes.